Professor Turun Padang: Enhancement of Productive Language Skills via Outdoor Learning Approach - Fatimah, Ali; Hafizoah, Kassim; Nur Syafawati, Sabuan; Rosjuliana Hidayu, Rosli; Mohd Shafierul Zaman, Abd Majid (Pusat Bahasa Moden (PBM), 2023)
3 December 2023 – The Centre for Modern Languages (CML) in collaboration with the Centre for Industry & Community Network (ICoN) successfully organized a corporate social responsibility (CSR) programme under the ‘Professor Turun Padang’ (PTP) initiative.